Implementing Practice Guidelines: A Workshop on Guidelines Dissemination and Implementation with a Focus on Asthma and COPD. (2006) - Boulet, Louis-Philippe; Becker, Allan; Bowie, Dennis; Hernandez, Paul; McIvor, Andrew; Rouleau, Michel; Bourbeau, Jean; Graham, Ian D; Logan, Jo; Légaré, France; Ward, Thomas F; Cowie, Robert L; et al.
Abstract : The present supplement summarizes the proceedings of the symposium "Implementing practice guidelines: A workshop on guidelines dissemination and implementation with a focus on asthma and COPD", which took place in Quebec City, Quebec, from April 14 to 16, 2005. This international symposium was a joint initiative of the Laval University Office of Continuing Medical Education (Bureau de la Formation Médicale Continue), the Canadian Thoracic Society and the Canadian Network for Asthma Care, and was supported by many other organizations and by industrial partners. The objectives of this meeting were to examine the optimal implementation of practice guidelines, review current initiatives for the implementation of asthma and chronic obstructive pulmonary disease (COPD) guidelines in Canada and in the rest of the world, and develop an optimal strategy for future guideline implementation. An impressive group of scientists, physicians and other health care providers, as well as policy makers and representatives of patients' associations, the pharmaceutical industry, research and health networks, and communications specialists, conveyed their perspectives on how to achieve these goals. This important event provided a unique opportunity for all participants to discuss key issues in improving the care of patients with asthma and COPD. These two diseases are responsible for an enormous human and socioeconomic burden around the world. Many reports have indicated that current evidence-based guidelines are underused by physicians and others, and that there are many barriers to an effective translation of recommendations into day-to-day care. There is therefore a need to develop more effective ways to communicate key information to both caregivers and patients, and to promote appropriate health behaviours. This symposium contributed to the initiation of what could become the "Canadian Asthma and COPD Campaign", aimed at improving care and, hence, the quality of life of those suffering from these diseases. It is hoped that this event will be followed by other meetings that focus on how to improve the transfer of key recommendations from evidence-based guidelines into current care, and how to stimulate research to accomplish this.